(untitled) (Communications in Mathematical Research, 2021)
In this paper we concern with the characterization of bounded linear operators S acting on the weighted Bergman spaces on the unit ball. It is shown that, if S satisfies the commutation relation ST_z_i = T_z_iS(i = 1, · · · , n), where T_z_i = z_if and T_z_i = P(z_if) where P is the weighted Bergman projection, then S must be a Hankel operator.